Impacts of COVID-19 Restrictions on Young Children's Outdoor Activity: A Systematic Review - Junjie Liu; Shirley Wyver; Muhammad Chutiyami (MDPI AG, 2022)
We sought to identify and synthesise available evidence to aid the understanding of the impact that COVID-19 restrictions had on the outdoor activity of children aged from birth to 12 years. Seven databases (Education Research Complete, ERIC, MEDLINE, PsycINFO, SPORTDiscus, Psychology and Behavioural Sciences Collection, WHO COVID-19 Database) were searched for relevant journal articles in English published from 2020 on. Four qualitative and eleven quantitative studies were included after screening. JBI's Critical Appraisal Tools were used for quality assessment. All qualitative studies showed an increase in outdoor activity. Less than half of the quantitative studies indicated an increase. Family demography, home characteristics, access to outdoor spaces, and parental support/encouragement/co-play were influential factors. The evidence also supports the recommendation for educators to increase children's outdoor play time to adhere to the physical distancing guidance and sanitisation requirements. Limited evidence suggests that when COVID-19 restrictions led to decreased outdoor activity, it was associated with less peer socialisation. We identified significant gaps in understanding of the impact of COVID-19 restrictions on young children's outdoor activity.